Sociotropy-autonomy, self-criticism and self-esteem in individuals with or without depression - Jhangir, Sahrash; Jameel, Rabia (Journal of the Pakistan Medical Association, 2023)
Objective: To examine and predict the relationship among sociotropy-autonomy, self-criticism and self-esteem in individuals with or without depression. Method: The cross-sectional, case-control study was conducted from November 2021 to July 2022 in various government hospitals and universities in Lahore, Pakistan, and comprised depression patients of either gender aged 20-40 years in group A. Healthy subjects matched for age and gender were enrolled in control group B. Data was collected using a demographic sheet predesigned in Urdu language, and the Urdu versions of Personal Style Inventory, Form of Self-Criticism/Attacking and Self-Reassuring Scale, and the Rosenberg Self-Esteem Scale. Data was analysed using SPSS 21. Results: Of the 200 subjects, 100(50%) were males, while each of the two groups had 100(50%) subjects. The overall mean age of the sample was 27.93±5.23 years. Sociotropy-autonomy had a significant positive relationship with self-criticism (p<0.01) and a significant negative relationship with self-esteem (p<0.01). Self-criticism was significantly negatively correlated with self-esteem (p<0.01). Sociotropy-autonomy was a significant predictor of self-criticism and self-esteem (p<0.01). Inter-group comparison of the levels of sociotropy-autonomy, self-criticism and self-esteem were significant (p<0.05). Conclusion: Sociotropy-autonomy was a highly significant predictor of self-criticism and self-esteem. People with depression had high sociotropy-autonomy and self-criticism scores, and low scores in self-esteem. Keywords: Sociotropy, Autonomy, Self-criticism, Self-esteem, Depression.